HUBUNGAN ANTARA TINGKAT PENGETAHUAN, SIKAP, DAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN MINUM OBAT PASIEN HIPERTENSI DI KELURAHAN PALMERAH KECAMATAN PALMERAH JAKARTA BARAT TAHUN 2020 - Salsabila Firdausia (2020)
The number of hypertension sufferers who recur and undergo hospitalization can indicate that the patients are less obedience in undergoing treatment. Obedience in undergoing medication is essential in order to achieve controlled blood pressure. An example of factor that can affect individual's obedience to treatment in family support. The patient's knowledge and attitude can also have an influence. The purpose of this study is to determine the relation between the level of knowledge, attitude, and family support with the level of hypertension patients' obedience to take medication in Palmerah Sub-District, Palmerah District, West Jakarta. This study is analytical observational with cross sectional design. The population used is hypertension patients in Palmerah Sub-District, Palmerah District, West Jakarta with samples of 110 people. The sampling technique that is used is simple random sampling. The research instrument used is questionnaires. The data analysis used in this study is univariate and bivariate analysis. Based on the chi-square test with a degree of trust (95%), it is shown that there is a relation between knowledge (p=0,000), attitude (p=0,000), and family support (p=0,000) with the obedience to take medication. The high level of knowledge, attitude, and family support can affect the level of obedience to take medication, because hypertension sufferers need their closest people who live in the same household so that they always enthusiastic when it comes to the undergoing treatment.